Intractable sneezing: is it always psychogenic? - Sulemanji, Mustafa N.; Kanbur, Nuray O.; Derman, Orhan; Pehlivantürk, Berna; Hoşal, Şefik A.; Şekerel, Bülent E. (The Turkish Journal of Pediatrics, 2011)
Intractable sneezing is not a commonly encountered disorder. The clinical presentation of such patients may cause the physician to undertake several tests before making a diagnosis. Are the performed analytic tests a waste of the health service funds or are they really sufficient? In this case, after undergoing several tests to rule out potential causes of the prevailing symptoms, psychiatric evaluation revealed a triggering event that contributed to the diagnosis of psychogenic sneezing. This specific case demonstrates why the diagnosis of psychogenic sneezing is difficult. An overwhelming number of such patients may be linked to a psychogenic cause; nevertheless, organic lesions or causes should be carefully excluded. Addressing the psychosocial issues through psychotherapy and coincidental use of locally administered anesthesia assisted in resolving the symptoms.